Informative content on social media pages: Study about digital practices on Facebook page of El-Bilad newspaper - ghezal, abderrazzek; bourahli, wafa; morzouglal, Ibrahim (Journal of Social Sciences and Humanities, 2021)
Digital publishing practices have become a necessary means in various social and functional fields, which applies to news publishing, which has created a new functional concept for social pages and professional practice; this study aims to describe the nature of digital publishing practices adopted by Journal El-Bilad on Facebook. Thus, use the virtual space of the social network facebook of El-Bilad newspaper as a research field; so we can classify this research into two types: Using social media as research tool & researching on activities & content of social media itself. The study revealed that the page does not improve the investment of technologies provided by the Facebook platform, nor does it make optimal use of them in developing digital publishing, which seem to be closely related to their traditional media practices.